2020
DOI: 10.1101/2020.05.15.20103275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying antibody kinetics and RNA shedding during early-phase SARS-CoV-2 infection

Abstract: Our ability to understand and mitigate the spread of SARS-CoV-2 depends largely on antibody and viral RNA data that provide information about past exposure and shedding. Five months into the outbreak there is an impressive number of studies reporting antibody kinetics and RNA shedding dynamics, but extensive variation in detection assays, study group demographics, and laboratory protocols has presented a challenge for inferring the true biological patterns. Here, we combine existing data on SARS-CoV-2 IgG, IgM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…A number of studies reported seroconversion for total antibody (combined IgG, IgM and/or IgA), [15][16][17][18][19][20][21] however the focus of findings presented is for specific antibody isotypes. For IgG, mean or median time to seroconversion ranged from 12 -15 days post symptom onset, 7,9,15,[22][23][24][25][26] with wide variation in first to last detection of IgG from 4 -73 days post symptom onset although reporting methods varied by study. 15,[27][28][29][30][31][32][33] For IgM, mean or median time to seroconversion ranged from 4-14 days post symptom onset, 7,9,15,[22][23][24]26,31,34 again with variations in reporting methods, study quality, and sample size giving rise to uncertainty around findings.…”
Section: Time To Seroconversionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies reported seroconversion for total antibody (combined IgG, IgM and/or IgA), [15][16][17][18][19][20][21] however the focus of findings presented is for specific antibody isotypes. For IgG, mean or median time to seroconversion ranged from 12 -15 days post symptom onset, 7,9,15,[22][23][24][25][26] with wide variation in first to last detection of IgG from 4 -73 days post symptom onset although reporting methods varied by study. 15,[27][28][29][30][31][32][33] For IgM, mean or median time to seroconversion ranged from 4-14 days post symptom onset, 7,9,15,[22][23][24]26,31,34 again with variations in reporting methods, study quality, and sample size giving rise to uncertainty around findings.…”
Section: Time To Seroconversionmentioning
confidence: 99%
“…Across the included studies, the majority of subjects developed detectable neutralising antibodies in response to SARS-CoV-2 infection in both human 7,18,22,29, and animal 41,[89][90][91][92] participants.…”
Section: Neutralising Antibody Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since December 2019, Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) has spread at an unprecedented speed and scale, resulting in 500,000 deaths, 11,500,000 diagnosed cases (as of 10/7/2020) 1 and likely many more undiagnosed cases with mild or no symptoms (10 fold) 2 . Nucleic acid (PCR) tests are widely used for clinical diagnosis and provide good estimates on the duration of viral shedding [3][4][5] . However, it remains uncertain how many people develop protective antibodies after recovery and for how long [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%